The Diane Elson Reader - Elson, Diane (Agenda Publishing Limited, 2025)
This volume brings together seminal papers and contributions from Diane Elson’s extensive back catalogue, including key contributions from the pre-digital era that are now difficult to find. The collection reflects the author’s enduring fascination with the interaction of gender, development and economics and the relevance of her thinking for tackling inequality and economic problems today.